Nurturing The Ecosystem of Hajj and Umrah Business in Indonesia: A Model For Development - Sopyan, Dedi; Maarif, M. Syamsul; Affandi, Joko; Arsyianti, Laily Dwi (Indonesian Journal of Business and Entrepreneurship, 2023)
As the country with the largest market share in the Hajj, Indonesia possesses the innate ability to contribute to the Hajj and Umrah ecosystem. Nevertheless, the management of this ecosystem is not yet optimized. This study aimed to formulate a model for developing Indonesia's commercial Hajj and Umrah ecosystems. The research was conducted from August 2021 to July 2022 at the Directorate General of Hajj and Umrah of the Ministry of Religion and the Head Office of the Hajj Financial Management Agency (BPKH). Interpretative structural modeling (ISM) was utilized to assess this study. The principal institutions or groups involved in constructing a model for developing Indonesia's Hajj and Umrah ecosystems were the DPR RI and the Ministry of Hajj in Saudi Arabia. The major obstacles encountered include the absence of an institution that focuses on optimizing the Hajj and Umrah ecosystems and the unpredictability of the Hajj and Umrah regulations that the Kingdom of Saudi Arabian government governs. Keywords: hajj financial management agency (bpkh), ecosystem, ministry of religion, hajj and umrah, soft system methodology